Analysis of The Russia-Ukraine War Based on Giulio Douhet's Airpower Theory and as The Best Practice For Indonesia's Air Force - Agus Kartomo; Tri Legionosuko; Helda Risman (Universitas Pertahanan Republik Indonesia (UNHAN RI), 2022)
The Russia-Ukraine war is a conventional war that happened in the modern era. The war shows that airpower is dominant in attacking strategic targets. Hight precision missiles use to avoid civilian casualties even though they still happen. From the perspective of airpower, it is exciting to analyze according to Giulio Douhet's theory. The result and discussions from the Russo-Ukrainian war from an air power perspective show that Douhet's theory is still relevant, but some adjustments are needed. Nowadays, attacking before declaring war breaks the war law. Making civilian casualties is against a human right. Another adjustment is due to technological advances in air power, so air power is a strategic target at the beginning of the war. This paper uses a descriptive-analytical method by analyzing data obtained from open sources.